Development Of A Fdtd Simulation Of Ionosphere Propagation For Earthquake Precursor Over The Sumatera-Malaysia Region - Yusoff, Siti Harwani Md (2018)
The perturbation on the vertical electric field in the ionosphere before large the large earthquake is a poorly investigated problem. The information obtaining from the electromagnetic (EM) wave propagated through the ionosphere can be applied to construct an earthquake precursor. This study conducted through the development of a home-grown 2D Finite Difference Time Domain (FDTD) code to simulate the EM propagation in the anisotropic ionosphere. To imitate the anisotropic and dispersive condition of the ionosphere, the electron density (